Psychotic disorders: comprehensive conceptualization and treatments - Tamminga, Carol A.; Ivleva, Elena I.; Reininghaus, Ulrich; Os, Jim van (Oxford University Press, 2021)
"The definition of psychotic spectrum disorders such as schizophrenia has evolved with changing nosogy and scientific advancements over the last 200 years. Understanding both the historical evolution of the concept as well as recent changes reflected in the American Psychiatric Association's Diagnostic and Statistical Manual (DSM-5) as well as the National Institute of Health's (NIH) Research Domain Criteria (RDOC) framework are critical for informing current efforts to further update and refine the nosology of psychotic spectrum disorders. This chapter offers an overview of past classification schemes, current standards, and novel approaches to further improve the validity of these definitions through use of biomarkers, reverse nosologies, and digital phenotyping tools like smartphones and sensors"--